KEPUASAN DAN LOYALITAS PETANI PADI TERHADAP PESTISIDA - Mustikarini, Fibria; Retnaningsih, Retnaningsih; Simanjuntak, Megawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2014)
Satisfaction and loyalty are important factors to mantain and to increase the level of sales. The purpose of this study was to analyze the satisfaction and loyalty to pesticides of paddy farmers. This study used crosssectional design with 100 farmers as samplesthat were chosen by simple random sampling in the village of Cikarawang, District Dramaga, Bogor, West Java. The data was collected by interview techniques using questionnaire.This research used one of pesticides brand that used by paddy farmers at study site. The results showed that the paddy farmers have already satisfied, this result was indicated by CSI value which was 79,14 percent and the proportion of loyalty level mostly in habitual buyer level as much as 41 percent farmers. The analysis revealed a significant positive correlation between the reference group of farmers and the satisfaction of farmers to the pesticides brand. In addition, there was also a significant positive correlation between the frequency of utilization and the brand loyalty of farmers. The model suggested that the family income per capita affect significantly on brand loyalty pesticides among paddy farmers.